IMPLEMENTATION OF ACADEMIC SUPERVISION BY SCHOOL PRINCIPALS TO ENHANCE PRIMARY SCHOOL TEACHERS' ABILITY IN UTILIZING DIGITAL MEDIA IN SOUTHWEST ACEH REGENCY - Mustika; Niswanto; Qismullah Yusuf (RADJA PUBLIKA, 2024)
The rapid development of digital technology in education forces teachers, willingly or not, to enhance their digital skills. School principals, as supervisors, can conduct academic supervision over their teachers to improve their ability in utilizing digital media. The aim of this research is to investigate the implementation of academic supervision programs for teachers to enhance their digital skills in Southwest Aceh Elementary Schools, covering planning, execution, and follow-up. This qualitative research gathers data through observation, interviews, and documentation. The subjects include six teachers and the school principals from three elementary schools in Southwest Aceh District. The findings indicate that: (1) academic supervision planning to enhance teachers' digital skills in Southwest Aceh District starts at the beginning of the academic year, involving all teachers. Principals initiate planning by analyzing teachers' needs, followed by budgeting, scheduling, and scalable evaluation. (2) Academic supervision in Southwest Aceh Elementary Schools is executed through direct visits and group discussions such as training, workshops, and seminars. (3) Follow-up actions involve continuous evaluation at regular intervals. (4) Challenges faced by Southwest Aceh Elementary Schools include limited understanding among older teachers, inadequate facilities and funding, and limited time, all of which affect the achievement of academic supervision goals.